2012
DOI: 10.1097/mog.0b013e32834bc9a9
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile infection

Abstract: The review aims to summarize the most recent evidence available on the epidemiology, risk factors and treatment of CDI. New antibiotics with selected action on C. difficile and limited effect on microflora (fidaxomicin) and donor fecal transplantation seem to have a relevant efficacy in treating CDI and reducing its recurrence. The use of selected monoclonal antibodies directed against C. difficile toxins in addition to standard therapy is a new, promising approach for the treatment of recurrent cases. Vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(85 citation statements)
references
References 94 publications
1
77
2
4
Order By: Relevance
“…For example, studies of the gut microbiome suggest that antibiotic administration can result in decreased diversity, which in some patients may be prolonged [16, 18, 38]; these patients are at increased risk of potentially life-threatening Clostridium difficile infections [3941]. Similarly, a recent study has reported that patients with more diverse sinonasal microbiomes have better postsurgical outcomes [29▪], establishing that the microbiome can serve at least as a disease modulator.…”
Section: Current Sinus Microbiome Literature Reviewmentioning
confidence: 99%
“…For example, studies of the gut microbiome suggest that antibiotic administration can result in decreased diversity, which in some patients may be prolonged [16, 18, 38]; these patients are at increased risk of potentially life-threatening Clostridium difficile infections [3941]. Similarly, a recent study has reported that patients with more diverse sinonasal microbiomes have better postsurgical outcomes [29▪], establishing that the microbiome can serve at least as a disease modulator.…”
Section: Current Sinus Microbiome Literature Reviewmentioning
confidence: 99%
“…The most important secondary risk factors include comorbidity or underlying conditions, inflammatory bowel diseases (IBDs), immunodeficiency and HIV, malnutrition, low serum albumin level (<2.5 g/dL), neoplastic diseases, cystic fibrosis, and diabetes [22]. Administration of broad-spectrum antimicrobials that impair the growth of normal flora and promote proliferation of toxigenic C. difficile remains the most widely recognized risk factor.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Any kind of antibiotics mainly clindamycin, cephalosporins, fluoroquinolones (moxifloxacin, gatifloxacin, and levofloxacin), ampicillin/amoxicillin, macrolides, co-trimoxazole, and tetracyclines can cause CDI. The exposure to metronidazole and vancomycin, which are used as the first choice drugs for treatment of CDI, may result in CDI themselves [21, 22]. …”
Section: Risk Factorsmentioning
confidence: 99%
“…The recurrence of CDI is difficult to treat, even with pulsed or tapered antibiotic (principally vancomycin-based) regimens. Patients who have recurrences become debilitated and carry out higher risk of severe CDI complications [23,29]. …”
Section: Fmt In CDImentioning
confidence: 99%